#### 2.1.3 Transport equation $$u_t+2 u_x = 0$$ IC $$u(-1,x)=\frac {x}{1+x^2}$$. Peter Olver textbook, 2.2.2 (b)

problem number 3

Taken from Peter Olver textbook, Introduction to Partial diﬀerential equations.

Solve for $$u(t,x)$$ in $$u_t+2 u_x = 0$$ with IC $$u(-1,x)=\frac {x}{1+x^2}$$

Mathematica

$\left \{\left \{u(t,x)\to \frac {-2 t+x-2}{4 t^2-4 t (x-2)+x^2-4 x+5}\right \}\right \}$

Maple

$u \left (t , x\right ) = \frac {-2 t +x -2}{\left (-2 t +x -2\right )^{2}+1}$

Hand solution

Solve $u_{t}+2u_{x}=0$ With initial conditions $$u\left ( -1,x\right ) =\frac {x}{1+x^{2}}$$.

Solution

Let $$u=u\left ( x\left ( t\right ) ,t\right )$$. Then \begin {equation} \frac {du}{dt}=\frac {\partial u}{\partial x}\frac {dx}{dt}+\frac {\partial u}{\partial t}\tag {2} \end {equation} Comparing (1),(2) shows that \begin {align} \frac {du}{dt} & =0\tag {3}\\ \frac {dx}{dt} & =2\tag {4} \end {align}

Eq (3) says that $$u$$ is constant on the chataterstic lines, or $$u=u\left ( x\left ( -1\right ) \right )$$. Using the given initial conditions, this becomes \begin {equation} u\left ( x\left ( t\right ) ,t\right ) =\frac {x\left ( -1\right ) }{1+x\left ( -1\right ) ^{2}}\tag {5} \end {equation} Eq (4) is now used to ﬁnd $$x\left ( -1\right )$$. Soving (4) gives $$x=x\left ( 0\right ) +2t$$. Hence $$x\left ( -1\right ) =x\left ( 0\right ) -2$$ or $$x\left ( 0\right ) =x\left ( -1\right ) +2$$. Therefore \begin {align*} x & =x\left ( -1\right ) +2+2t\\ x\left ( -1\right ) & =x-2-2t \end {align*}

Now that we found $$x\left ( -1\right )$$, we substitute it in (5), giving the solution$u\left ( x\left ( t\right ) ,t\right ) =\frac {x-2-2t}{1+\left ( x-2-2t\right ) ^{2}}$ Alternative method. Using Lagrange-charpit method

$\frac {dt}{1}=\frac {dx}{2}=\frac {du}{0}$ Which implies that $$du=0$$ or $$u=C_{1}$$. A constant. Integrating $$\frac {dt}{1}=\frac {dx}{2}$$ gives $$t=\frac {1}{2}x+C_{2}$$ or $$C_{2}=t-\frac {1}{2}x$$. But $$C_{1}=F\left ( C_{2}\right )$$ always, where $$F$$ is arbitrary function. Since $$C_{1}=u$$ then\begin {align} u & =F\left ( C_{2}\right ) \nonumber \\ u & =F\left ( t-\frac {1}{2}x\right ) \tag {1} \end {align}

At $$t=-1$$ the above becomes$\frac {x}{1+x^{2}}=F\left ( -1-\frac {1}{2}x\right )$ Let $$-1-\frac {1}{2}x=z$$ which implies $$x=-2\left ( 1+z\right )$$ The above can be written as\begin {align*} \frac {-2\left ( 1+z\right ) }{1+\left ( -2\left ( 1+z\right ) \right ) ^{2}} & =F\left ( z\right ) \\ F\left ( z\right ) & =-\frac {2\left ( 1+z\right ) }{4z^{2}+8z+5} \end {align*}

From the above then (1) can be written as\begin {align*} u\left ( t,x\right ) & =-\frac {2\left ( 1+\left ( t-\frac {1}{2}x\right ) \right ) }{4\left ( t-\frac {1}{2}x\right ) ^{2}+8\left ( t-\frac {1}{2}x\right ) +5}\\ & =\frac {x-2t-2}{4t^{2}-4tx+8t+x^{2}-4x+5}\\ & =\frac {x-2t-2}{1+\left ( x-2-2t\right ) ^{2}} \end {align*}

The following is an animation of the solution

 3D 2D

Source code used for the above  ________________________________________________________________________________________